2020
DOI: 10.33137/ijidi.v4i3/4.33554
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Inclusivity, Social Responsibility Aspects, and Outcomes of a Mobile Digital Library and Information Service Model for a Developing Country

Abstract: The provision of library services through rigid compartmentalisation of academic, public, school, and special libraries operating in one country can be cost-effective if a country has strong socio-economic, cultural, educational, and political structures. This arrangement is apparently a fallacy for countries that lack such structures, as is the case with Lesotho. This study examined the outcomes and the impact of the UNESCO-funded project titled Distance and Rural Learner-Teacher Support through a Mobile Digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Looking for the studies about local information professionals' roles we can point out that the earliest mentions are related to local history work in public libraries. Reed 25 has suggested that the role of the local history librarian can be indicated as the manager of the local history collections and services for providing access to the public library users, which include researchers, local historians, students, local inhabitants, and other interested persons. Reed has pointed out the uniqueness of this work, claiming that "[i]f the local history librarian does not collect it, then no one else will" 26 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Looking for the studies about local information professionals' roles we can point out that the earliest mentions are related to local history work in public libraries. Reed 25 has suggested that the role of the local history librarian can be indicated as the manager of the local history collections and services for providing access to the public library users, which include researchers, local historians, students, local inhabitants, and other interested persons. Reed has pointed out the uniqueness of this work, claiming that "[i]f the local history librarian does not collect it, then no one else will" 26 .…”
Section: Literature Reviewmentioning
confidence: 99%